2007
DOI: 10.14488/1676-1901.v7i1.100
|View full text |Cite
|
Sign up to set email alerts
|

Sistema De Produção Flexível E Intensificação Do Trabalho: Um Ensaio Teórico

Abstract: A forma como o trabalho está organizado atualmente é resultado de um processo de mutações que tem por exigências empresas mais flexíveis. Para isso, as empresas se reestruturaram e o "modelo" mais difundido da reestruturação produtiva, é a produção flexível, tida como um processo produtivo eficiente para a recuperação dos níveis de acumulação e exigências do mercado. Este modelo de gestão permitiu ao capital gerenciar a força de trabalho de maneira mais flexível, o que ocasionou um certo grau de intensificação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…7 In addition , it is observed that professional demands and rising unemployment , coupled with the competitive system , make workers increasingly anxious and sick , and many of them seek treatment for psychosomatic problems developed as a result of this competitive situation. 8 Thus, it appears that the professional has undergone a great physical and psychological. It is noteworthy that the worker, most often presents difficulties to identify what is happening in your life and your health.…”
mentioning
confidence: 99%
“…7 In addition , it is observed that professional demands and rising unemployment , coupled with the competitive system , make workers increasingly anxious and sick , and many of them seek treatment for psychosomatic problems developed as a result of this competitive situation. 8 Thus, it appears that the professional has undergone a great physical and psychological. It is noteworthy that the worker, most often presents difficulties to identify what is happening in your life and your health.…”
mentioning
confidence: 99%